Amphiphilic phospholipid–iodinated polymer conjugates for bioimaging. (15th June 2021) - Djorgbenoo, Richmond; Rubio, Mac Michael M.; Yin, Ziyu; Moore, Keyori J.; Jayapalan, Anitha; Fiadorwu, Joshua; Collins, Boyce E.; Velasco, Brian; Allado, Kokougan; Tsuruta, James K.; Gorman, Christopher B.; Wei, Jianjun; et al.
Abstract : Amphiphilic phospholipid–iodinated polymer conjugates were designed and synthesized as new macromolecular probes for a highly radiopaque and biocompatible imaging technology. Abstract : Amphiphilic phospholipid–iodinated polymer conjugates were designed and synthesized as new macromolecular probes for a highly radiopaque and biocompatible imaging technology. Bioconjugation of PEG 2000-phospholipids and iodinated polyesters by click chemistry created amphiphilic moieties with hydrophobic polyesters and hydrophilic PEG units, which allowed their self-assemblies into vesicles or spiked vesicles. More importantly, the conjugates exhibited high radiopacity and biocompatibility in in vitro X-ray and cell viability measurements. This new type of bioimaging contrast agent with a M n value of 11 289 g mol −1 was found to have a significant X-ray signal at 3.13 mg mL −1 of iodine equivalent than baseline and no cytotoxicity after 48 hours incubation of with HEK and 3T3 cells at 20 μM (20 picomoles) concentration of conjugates per well. The potential of adopting the described macromolecular probes for bioimaging was demonstrated, which could further promote the development of a field-friendly and highly sensitive bioimaging contrast agent for point-of-care diagnostic applications.